Petrography, geochemistry and Pb isotopic signature of banded iron formations associated with the genesis of the caves and iron ore of Serra Sul, Carajás, Pará, Brazil - Cabral, Erica da Solidade; Mambira, Joel Buenano; Toro, Marco Antonio Galarza (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Petrographic, geochemical and isotopic studies in caves in banded iron formations of the S11D body, Serra Sul, were fundamental to understand the process of formation of caves and its relation with the genesis of iron ore. Collected rocks are in different stages of alteration in time: non-altered jaspilito, altered jaspilito and iron ore, thus establishing a profile of weathering. From the base to the top, there was a sharp decrease in SiO2 content and a relative increase in Fe2O3T content. Pb-Pb isotopic analyzes indicate homogeneous values with isotopic signature similar to the rocks of the upper crust. The values obtained suggest little radiogenic rocks when compared with the Pb-Pb isotopic signatures of the Carajás Cu-Au deposits. No isotopic changes were identified that indicated metamorphic events, tectonic reactivations or percolation of hydrothermal fluids that disturbed the Pb-Pb geochronometer. Such evidence suggests that the formation of caves and iron ore is related only to the supergenic processes associated with the development of a weathering profile.